2015
DOI: 10.3390/su71014230
|View full text |Cite
|
Sign up to set email alerts
|

Urban Lighting Project for a Small Town: Comparing Citizens and Authority Benefits

Abstract: Abstract:The smart and resilient city evolves by slow procedures of mutation without radical changes, increasing the livability of its territory. The value of the city center in a Smart City can increase through urban lighting systems: its elements on the territory can collect and convey data to increase services to city users; the electrical system becomes the so-called Smart Grid. This paper presents a study of smart lighting for a small town, a touristic location inside a nature reserve on the Italian coast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…A study performed by the European Commission has shown that between 30% and 50% of electricity used for lighting could be saved by investing in energy-efficient lighting systems [18]. In Spain, in some municipalities, the consumption of energy in public lighting reaches up to 80% of the total electricity consumption.…”
Section: Lightingmentioning
confidence: 99%
“…A study performed by the European Commission has shown that between 30% and 50% of electricity used for lighting could be saved by investing in energy-efficient lighting systems [18]. In Spain, in some municipalities, the consumption of energy in public lighting reaches up to 80% of the total electricity consumption.…”
Section: Lightingmentioning
confidence: 99%
“…Escolar et al [13] sought to improve the quality of street lighting in Spain. Cellucci et al [14] studied smart lighting in a small town. Salata et al [15] made an economic and investment assessment of safety and emergency lighting in road tunnels.…”
Section: Introductionmentioning
confidence: 99%
“…Measures, such as installing additional security lighting or increasing the luminous flux of existing security lighting, can be considered to solve such problems. However, maintaining bright security lighting throughout the night consumes considerable lighting energy and results in light trespass to nearby residents, which can cause sleeping disorders and privacy infringement [6][7][8]. These issues can be solved by providing brighter light only at those locations and times in which a bright luminous environment is needed.…”
Section: Introductionmentioning
confidence: 99%